ANALISIS TRAFIK SUARA JARINGAN KOMUNIKASI TELEPON PT. BADAK NGL BONTANG – KALIMANTAN TIM - Ajulian Zahra, Ajub; Giri Laksono, Nur Muhammad (Diponegoro University, 2009)
In time being, the user of telecommunication provider is growing up, both of voice and datatelecommunication, so it is needed to design a good and accurate telecommunication tools to avoidproblem’s user. In this case, PT. Badak NGL Bontang needs to review the telecommunication tools(number of trunk) because of reducing the number of employee for re-organization.In this paper, application programme is made to analyze voice traffic data with the result that to determineoptimalization number of trunk. Work and condition of system in traffic analysis is influenced by trafficparameters, like ASR (Answered Seizure Ratio), SCH (Seizure per Circuit per Hour), MHTS (MeanHolding Time per Seizure), dan GOS (Grade of Service).From traffic analysis, optimalization number of trunk is 33 trunks with the value of grade of service is 0,1%., so the efficiency number of trunk in PT. Badak NGL is 41,25 % which is determined from comparisonthe number of trunk in traffic analysis (33 trunks) and the number of trunk in PT. Badak NGL Bontang (80trunks), so with 33 trunks, the probability of blocking is still low. In traffic analysis, the condition of systemwill be busy if the value of real grade of service is higher than the value of grade of service which isdetermined, and the condition of system will be normal if the value of real grade of service is lower thanthe value of grade of service which is determined.